PENDIDIKAN AGAMA KATOLIK BERBASIS MODUL AJAR DENGAN MENGGUNAKAN METODE KNOW, SHARE, MEET, EXPRESS - Permana, Natalis Sukma; More, Christoforus Purnama (Bahasa Indonesia, 2025)
This development research aims to: 1) determine the procedure for developing a teaching module using the KSME method on the material of 'Realizing Faith in the Middle of Society. 2) Determine the feasibility level of Catholic Religious Education teaching module products using the KSME method on the material of Realizing Faith in the Middle of Society. This development research was conducted using the Research and Development (R&D) research method with the ADDIE developer model. The development steps are grouped into five stages, namely: 1) analysis stage, 2) design stage, 3) development stage, 4) implementation stage, and 5) evaluation stage. Product trials were designed through initial trials and field trials. In the initial trial, the validity of the product was tested by material experts and media experts, as well as a limited trial by five students. Following the initial trial, a field trial was conducted involving 23 students. Data collection was carried out by observation, interview, and questionnaire using a Likert scale. The data analysis technique employed in this research is descriptive analysis. The results of this development research are in the form of a teaching module using the KSME method on the material of Realizing Faith in Society. Teaching modules using the KSME method are rated “very feasible” based on the results of the product validity test. Based on the student response questionnaire data in the limited trial, it falls into the “powerful” category. Meanwhile, based on the student response questionnaire data in the field trial, it is in the "Very Strong" category.